Methods and results of local treatment of brain metastases in patients with breast cancer - Szadurska, Agnieszka; Pluta, Elżbieta; Walasek, Tomasz; Blecharz, Paweł; Jakubowicz, Jerzy; Mituś, Jerzy W. (Contemporary Oncology/Współczesna Onkologia, 2016)
This article presents methods and results of surgical treatment and radiation therapy of brain metastases in breast cancer patients (brain metastases from breast cancer BMF-BC). Based on the literature data, it was shown that patients with single BMF-BC, aged less than 65 years, with Karnofsky score (KPS) of 70 or more and with cured or controlled extracranial disease are the best candidates to surgical treatment. Irrespective of the extracranial disease control status, there are indications for surgery in patients with symptomatic mass effect (tumour diameter larger than 3 cm) and patients with obstructive hydrocephalus from their BMF-BC. Stereotactic radiosurgery (SRS) has some advantages over surgery, with similar effectiveness: it may be used in the treatment of lesions inaccessible to surgery, the number of lesion is not a limiting factor if each lesion is small (< 3) and adequate doses can be delivered, it is not contraindicated in patients with active extracranial disease, it does not interfere with ongoing systemic treatment, and it does not require general anaesthesia or hospitalisation. A disadvantage of SRS, as compared to whole brain radiotherapy (WBRT), in patients with BMF-BC is the possibility of subsequent development of new lesion in the non-irradiated field. Thus the majority of the BMF-BC patients are not good candidates to surgery or SRS; WBRT alone or combined with a systemic treatment still plays a major role in the treatment of these patients.